The impact of bullying and cyberbullying on mental health: a systematic review - Agustiningsih, Nia; Yusuf, Ah; Ahsan, Ahsan; Fanani, Qori (Intelektual Pustaka Media Utama, 2024)
Bullying, including cyberbullying, has a devastating impact on mental health, particularly among adolescents. This literature study aims to identify mental health issues caused by bullying and cyberbullying. A systematic review was conducted in the last five years using the keywords